Comparison behavior of a large turbo machine vibration between unbalance and bent shaft - Thanh, Ngo Van (Vietnam Journal of Science and Technology, 2016)
In recently, large capacity steam turbines have come into wider use and have been designed to ever higher performance specifications. As we all know, it’s hard to maintain the concentricity of a rotor-bearing system during operating, especially for multi-rotors within specified level of vibration. Rotor vibration could be caused by many reason, mass unbalance and bent shaft are amongst almost frequently occurring. Mass unbalance and bent shaft both give to force excitation at a frequency corresponding to once per revolution. Taking a LP B rotor of a 1000MW USC steam turbine as an example, this paper studies the lateral vibration of the LP B rotor based on finite element. Responses of mass unbalance and bent shaft are analyzed and compared.